2015
DOI: 10.1146/annurev-virology-100114-054846
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Consequences of Calcium-Conducting Viroporins

Abstract: Eukaryotic cells have evolved a myriad of ion channels, transporters, and pumps to maintain and regulate transmembrane ion gradients. As intracellular parasites, viruses also have evolved ion channel proteins, called viroporins, which disrupt normal ionic homeostasis to promote viral replication and pathogenesis. The first viral ion channel (influenza M2 protein) was confirmed only 23 years ago, and since then studies on M2 and many other viroporins have shown they serve critical functions in virus entry, repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 136 publications
0
101
0
Order By: Relevance
“…During infection with Dengue virus (DENV), host cells undergo a series of detrimental functional changes, including profound remodelling and redistribution of cell membrane structures, 1,4 which gives rise to nucleus-like structures referred to as "viral factories." 2 In many cases, this phenomenon is mediated by viroporin, a family of small viral protein, which contain highly hydrophobic domains that can form amphipathic alpha helices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During infection with Dengue virus (DENV), host cells undergo a series of detrimental functional changes, including profound remodelling and redistribution of cell membrane structures, 1,4 which gives rise to nucleus-like structures referred to as "viral factories." 2 In many cases, this phenomenon is mediated by viroporin, a family of small viral protein, which contain highly hydrophobic domains that can form amphipathic alpha helices.…”
mentioning
confidence: 99%
“…3 Indeed, viroporins may be virulence factors encoded by members of diverse families of RNA and DNA viruses of clinical interest, including hepatitis C virus (HCV), human immunodeficiency virus (HIV-1), human papilloma virus (HPV), influenza A virus (IAV), coronaviruses, picornaviruses (polioviruses), and togaviruses (see ref. 4 for a comprehensive review).…”
mentioning
confidence: 99%
“…Both RV and PV deplete ER Ca 2+ stores through expression of viroporins (RV NSP4 and PV 2B proteins) that target the ER and this reduces PLC/IP3-dependent Ca 2+ signaling (9). We tested the response to ATP in RV-infected MA104-GCaMP5G/RCEPIA er and poliovirus-infected HeLa-GCaMP6s/RCEPIA er cells and the results of a representative experiment are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The specific changes in Ca 2+ homeostasis are different between different viral systems, but in general viruses often cause an elevation in the concentration of cytosolic Ca 2+ ([Ca 2+ ] c ) in conjunction with either depletion of endoplasmic reticulum Ca 2+ ([Ca 2+ ] ER ) stores [e.g., rotavirus (RV)] or elevation of [Ca 2+ ] ER leading to disruption in Ca 2+ signaling between the ER and mitochondria (e.g., hepatitis B virus) (58). More recent studies have demonstrated that virus-induced Ca 2+ signaling can activate cellular processes, such as store-operated Ca 2+ entry (SOCE), fluid secretion to cause diarrhea and serotonin release to cause vomiting, activation of the inflammasome leading to proinflammatory cytokine release, induction of the autophagy pathway, and disruption of the host cell’s cytoskeleton (9). To characterize the roles Ca 2+ signaling plays in virus replication and pathogenesis for these viruses, virologists have capitalized on the development of live cell Ca 2+ imaging technology to track changes in Ca 2+ levels during infection and to determine the molecular mechanisms used by viruses to induce these signals.…”
Section: Introductionmentioning
confidence: 99%
“…An alteration in cellular calcium homeostasis is critical for rotavirus replication and cytopathogenesis, and this has been correlated with the NSP4 viroporin [see review in Hyser and Estes (2015)]. Earlier studies reported that NSP4 colocalize with the autophagosome marker LC3 in "cap-like structures" associated with viroplasms (Berkova et al 2006), sparking interest of whether the host autophagy machinery is manipulated during rotavirus infection.…”
Section: Rotavirus Nsp4mentioning
confidence: 99%